Respiratory management in severe acute respiratory syndrome coronavirus 2 infection. Issue 3 (April 2020) - Price, Susanna; Singh, Suveer; Ledot, Stephane; Bianchi, Paolo; Hind, Matthew; Tavazzi, Guido; Vranckx, Pascal
The severe acute respiratory syndrome coronavirus 2 pandemic is to date affecting more than a million of patients and is challenging healthcare professionals around the world. Coronavirus disease 2019 may present with a wide range of clinical spectrum and severity, including severe interstitial pneumonia with high prevalence of hypoxic respiratory failure requiring intensive care admission. There has been increasing sharing experience regarding the patient's clinical features over the last weeks which has underlined the need for general guidance on treatment strategies. We summarise the evidence existing in the literature of oxygen and positive pressure treatments in patients at different stages of respiratory failure and over the course of the disease, including environment and ethical issues related to the ongoing coronavirus disease 2019 infection.